Studies on N Mineralization from Soils Amended with Green Manures under the Influence of Two Different Moisture Regime - Biswas, Sujan; Ghosh, Arunava; Sinha, Abhas Kumar; Mukhopadhyay, Prabir (International Journal of Bio-resource and Stress Management, 2023)
A laboratory experiment was conducted over 12 weeks to study the nitrogen (N) mineralization pattern and kinetics from nine locally available green manure (GM) at submergence and field capacity (FC), when incorporated into typical rice growing teesta alluvial soils of the district Coochbehar located at Terai Agro-climatic region of West Bengal. Rapid mineralization was evidenced by the fact that out of total N mineralized at the end of incubation, 20.43-100.59% and 27.60-76.17% released during 1st week at submergence and FC, respectively. After 12 weeks highest N was mineralized from C. sophera (162.57 mg kg-1 soil) and G. sepium (195.72 mg kg-1 soil) amended soil at submerge and FC moisture condition, respectively. At submergence, soils amended with I. cornea and V. ungiculata and at FC, G. sepium and E. indica amended soil exhibited most consistent trend of successive increase till the end with a few exception; whereas mean (of moisture regime) cumulative mineralization showed most consistency in case of V. ungiculata and C. sophera. Mean (of GM) cumulative mineralization was better at submergence over FC moisture regime during early period; whereas reverse was the trend during later period of incubation. Similar was the trend for individual GMs except C. sophera, G. sepium and I. cornea recording higher value at FC almost all throughout the incubation period. FC moisture regime recorded higher mineralization potential (N0) and lower rate constant (k) for all GMs; except N0 value for P. pinnata. Considering all these above C. sophera and V. ungiculata were identified as best GM species across moisture regime as well as at submergence; whereas at FC moisture regime G. sepium and E. indica were best performing GM species.